Food addiction in patients on weight loss treatment - Palacio, Ana Cristina; Cuello, Catalina; Díaz-Torrente, Ximena (Frontiers in Nutrition, 2024)
Background: Food addiction (FA) is defined as hedonic eating behavior involving the consumption of highly palatable foods (i.e., ultra processed foods in quantities beyond homeostatic energy requirements). FA is present in a subset of patients with overweight or obesity and could contribute to the response to weight loss treatments. Aim: Determine food addictionFA in individuals that fulfil the criteria of FA as measured by the YFAS 2.0, and its association with anthropometric and body composition variables in a clinical sample of patients undergoing weight loss treatment. Also, to determine the most prevalent FA criteria. Methods: An observational, analytical, and cross-sectional study was conducted. Sampling was non-probabilistic, convenience based. A total of 158 participants were recruited from two clinical centers (private and public) focused on managing noncommunicable chronic diseases. The Chilean version of YFAS 2.0 was administrated through the online REDCap platform. Anthropometric measurements were measured, and body mass index (BMI) was calculated. Results: The mean age was 47.8 (SD 14.9) and BMI 28.7 (SD 5.3) kg/m 2 . There were (12.7%) patients who screened positive on the YFAS 2.0 Chilean version (3.2% for mild, 2.5% for moderate and 7.0% for severe), and the mean symptom count was 2.2 (SD 2.6), with withdrawal being the most prevalent criterion (33.5%). FA patients had significantly higher body weight compared to non-FA subjects (p=0.045). We observed a slight and significant correlation between FA symptom count and body weight (p=0.020), waist circumference (p=0.005), and BMI (p=0.023). Conclusion: This is the first study in Chile that showed that FA was present in patients undergoing weight loss treatment and was associated with anthropometric measurements. In addition, it showed that withdrawal was the most prevalent criterion. Future studies should investigate whether the presence of FA and the withdrawal criterion could contribute to suboptimal clinical response to weight loss treatment.